Women's rights in the law general international (Journal of the College of Basic Education, 2022)
Caring for women is considered caring for society, and preserving and protecting them is a protection for society's values ​​and morals.Therefore, Islam respected the woman and worked to preserve her and preserve her dignity, considering it a basis for the formation ofSociety has given it rights unless it is granted by all positive laws. Islamic legislation has recognized the principle ofEquality among all people is equality in an actual and practical manner between all human beings, male and female, the Almighty said:  ﭵﭶ ﭷ ﭸ ﭹ ﭺ ﭻ ﭼ ﭽ ﭾ ﭿﮀ ﮁ ﮂ ﮃ ﮄ ﮅﮆ ﮇ ﮈ ﮉ ﮊ (1 ) This is the principle that came